Fragmentation and connectivity of the natural cover at county level in Costa Rica, during 2000 and 2015 years - Morera_Beita, Carlos (2019)
This research proposes the formulation of a fragmentation / connectivity index that assesses the condition of natural cover at the canton level for Costa Rica based on spatial distribution considering the variables: area of the county, the natural coverage area, the number of fragments and distance of neighborhood between the fragments of the natural cover, for the years 2000 and 2015. The images Landsat 7 for the year 2000 and Landsat 8 for the year 2015 were used where the land use categories for each year were derived through supervised classification with ERDAS software and with ArcMap10.5 biometric indices were estimated using the Vargas equation (2008) which was modified for its application. Within the results, we identified the cantons that present greater or lesser fragmentation and connectivity of their natural coverage during the study period.